Dimensional Reduction and Scattering Formulation for Even Topological Invariants - Schulz-Baldes, Hermann; Toniolo, Daniele (Communications in Mathematical Physics, 2021)
Strong invariants of even-dimensional topological insulators of independent Fermions are expressed in terms of an invertible operator on the Hilbert space over the boundary. It is given by the Cayley transform of the boundary restriction of the half-space resolvent. This dimensional reduction is routed in new representation for the K-theoretic exponential map. It allows to express the invariants via the reflection matrix at the Fermi energy, for the scattering set-up of a wire coupled to the half-space insulator.
CRIS-Team Scopus Importer:2020-11-20

Time-dependent topological systems: A study of the Bott index - Toniolo, Daniele (Physical Review B - Condensed Matter and Materials Physics, 2018)
The Bott index is an index that discerns among pairs of unitary matrices that can or cannot be approximated by a pair of commuting unitary matrices. It has been successfully employed to describe the approximate integer quantization of the transverse conductance of a system described by a short-range, bounded, and spectrally gapped Hamiltonian on a lattice on a finite two-dimensional torus and to describe the invariant of the Bernevig-Hughes-Zhang model even with disorder. This paper shows the constancy in time of the Bott index and the Chern number related to the time-evolved Fermi projection of a system described by a short-range, bounded, and time-dependent Hamiltonian that is initially gapped. The general situation of a ramp of a time-dependent perturbation is considered, a section is dedicated to time-periodic perturbation